1995
DOI: 10.1016/1074-7613(95)90058-6
|View full text |Cite
|
Sign up to set email alerts
|

A novel leukointegrin, αdβ2, binds preferentially to ICAM-3

Abstract: The leukocyte-restricted beta 2 (CD18) integrins mediate cell adhesion in a variety of events essential for normal immune function. Despite extensive research in this field, only three members of this integrin subfamily have been described: CD11a/CD18 (LFA-1), CD11b/CD18 (Mac-1), and CD11c/CD18 (p150,95). We have identified a cDNA encoding a fourth alpha chain, alpha d, that associates with CD18. The alpha d subunit is more closely related to CD11b and CD11c than to CD11a. This integrin is expressed at moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
197
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 243 publications
(205 citation statements)
references
References 31 publications
5
197
2
Order By: Relevance
“…Alternatively, it may represent a feature of the memory phenotype of T cells recruited into the synovium. Expression of this molecule on the myeloid lines HL60 and THP-1 is reduced by stimulation with PMA, whereas expression of CDllb and CDllc is increased (6). Studies of a d levels in both PBL and synovium from RA patients, as well as comparisons with other inflammatory states, will be needed to further clarify this issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, it may represent a feature of the memory phenotype of T cells recruited into the synovium. Expression of this molecule on the myeloid lines HL60 and THP-1 is reduced by stimulation with PMA, whereas expression of CDllb and CDllc is increased (6). Studies of a d levels in both PBL and synovium from RA patients, as well as comparisons with other inflammatory states, will be needed to further clarify this issue.…”
Section: Discussionmentioning
confidence: 99%
“…ad/ CDl8 is expressed at very low levels. Granulocytes and monocytes express high levels of CDllb, with lower levels of CDlla, CDllc, and ad (4,6,19). Stimulation of granulocytes with phorbol myristate acetate (PMA) or FMLP results in a rapid increase in the levels of a d expression, consistent with mobilization of an intracellular pool of a d in these cells (6).…”
mentioning
confidence: 99%
“…However, the pattern of expression of this integrin is unique among other myeloid cellspecific ␤ 2 integrins in that ␣ D ␤ 2 is expressed poorly on peripheral blood leukocytes but strongly on macrophage foam cells within atherosclerotic plaques. 1,2 In contrast, the major myeloid-specific integrin ␣ M ␤ 2 is progressively up-regulated on circulating neutrophils and monocytes in response to chemotactic stimulation 3,4 and is down-regulated in lesion-derived macrophages. 5 The significance of the up-regulation of ␣ D ␤ 2 in monocyte-derived cells from atherosclerotic lesions is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that ␣ D ␤ 2 is capable of binding vascular cell adhesion molecule 1 (VCAM-1) 6,7 and intercellular adhesion molecule 3 (ICAM-3). 1 VCAM-1 is present on endothelial cells and, thus, clearly absent from the extravascular compartment in which formation of foam cells occurs. ICAM-3 is present on lymphocytes that are detectable in atherosclerotic lesions (for a review, see Getz 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since CD11a and DC-SIGN do not appear to interact with ICAM-3 (Figures 1 and 2), we subsequently evaluated whether CD11d, known to show a preferential binding to ICAM-3, 8 could instead function as ICAM-3 counterreceptor in our system. Because of the absence of commercially available Abs displaying CD11d blocking properties, we performed confocal microscopy studies and found a strong constitutive expression of CD11d by slanDC and NK cells, while neutrophils were nearly negative ( Figure 3A).…”
Section: Icam-3 Clusters and Co-localizes With Cd11d Within The Contamentioning
confidence: 99%